2009
DOI: 10.1080/17470210701855520
|View full text |Cite
|
Sign up to set email alerts
|

Why do people show minimal knowledge updating with task experience: Inferential deficit or experimental artifact?

Abstract: Students generally do not have highly accurate knowledge about strategy effectiveness for learning, such as that imagery is superior to rote repetition. During multiple study-test trials using both strategies, participants' predictions about performance on List 2 do not markedly differ for the two strategies, even though List 1 recall is substantially greater for imagery. Two experiments evaluated whether such deficits in knowledge updating about the strategy effects were due to an experimental artifact or to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…Interestingly, the fact that older adults recalled more middle pairs with imagery than sentence suggests that the lesser utilization of imagery is not due to the efficiency of each strategy. Hertzog et al (2009) found that knowledge about the superiority of imagery over rote repetition during associative learning was relatively low for participants. Thus, despite our finding about effectiveness of each strategy, older adults might have a false perception of how efficient imagery use is, which makes them reticent to use imagery.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, the fact that older adults recalled more middle pairs with imagery than sentence suggests that the lesser utilization of imagery is not due to the efficiency of each strategy. Hertzog et al (2009) found that knowledge about the superiority of imagery over rote repetition during associative learning was relatively low for participants. Thus, despite our finding about effectiveness of each strategy, older adults might have a false perception of how efficient imagery use is, which makes them reticent to use imagery.…”
Section: Discussionmentioning
confidence: 92%
“…It seems that participants did not update their metacognitive judgments within one passage (i.e., after completing the proofreading task) or between passages (i.e., having task experience with a prediction-proofreadingpostdiction session already completed), which is inconsistent with Dunlosky and Hertzog (2000), in which participants became more accurate in their metacognitive judgments with task experience. However, Dunlosky and Hertzog (2000) did find that difference scores contrasting performance with predictions and postdictions were worse for the second list than the first list, such that people became more underconfident in their performance when using interactive imagery to study paired-associates (see also Hertzog et al, 2009;Price, Hertzog, & Dunlosky, 2008). In the present study, it may be necessary to have direct feedback or several trials (more than just two) in which participants become more aware of their performance, and what factors influence the strategies that are used during proofreading and when making metacognitive judgments.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, many college students report that blocking is better (Kornell & Bjork, 2008), in which case participants may prefer to block their study. In Kornell and Bjork's study, however, students' beliefs about these strategies were measured after they had performed the task, and beliefs can be substantially different when assessed prior to (or during) task completion versus after the task is complete (e.g., Hertzog et al, 2009). Thus, whether people's study choices would reflect a preference for blocking or interleaving was an unresolved issue.…”
mentioning
confidence: 99%